In‐depth proteomic analyses of exosomes isolated from expressed prostatic secretions in urine. Issue 10 (23rd April 2013) - Principe, Simona; Jones, E. Ellen; Kim, Yunee; Sinha, Ankit; Nyalwidhe, Julius O.; Brooks, Jasmin; Semmes, O. John; Troyer, Dean A.; Lance, Raymond S.; Kislinger, Thomas; Drake, Richard R.
Abstract : Expressed prostatic secretions (EPS) are proximal fluids of the prostate that are increasingly being utilized as a clinical source for diagnostic and prognostic assays for prostate cancer (PCa). These fluids contain an abundant amount of microvesicles reflecting the secretory function of the prostate gland, and their protein composition remains poorly defined in relation to PCa. Using expressed prostatic secretions in urine (EPS‐urine), exosome preparations were characterized by a shotgun proteomics procedure. In pooled EPS‐urine exosome samples, ∼900 proteins were detected. Many of these have not been previously observed in the soluble proteome of EPS generated by our labs or other related exosome proteomes. We performed systematic comparisons of our data against previously published, prostate‐related proteomes, and global annotation analyses to highlight functional processes within the proteome of EPS‐urine derived exosomes. The acquired proteomic data have been deposited to the Tranche repository and will lay the foundation for more extensive investigations of PCa derived exosomes in the context of biomarker discovery and cancer biology.